Assessing the Impact of the Audit Report on Allegations of Corruption Cases - Haryanto Haryanto; Niken Latifatuz Zahra; Agung Juliarto; Wahyu Meiranto (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the impact of the external audit results on the alleged corruption case. Research Design and Methodology: The alleged corruption case is measured by the number of cases reported to the High Prosecutor’s Office. The unit of analysis comprises alleged corruption cases in all regencies and municipalities in Central Java Province, with a total of 210 observations collected over six years from 2018 to 2023. Panel data regression is employed as the analytical method. Findings and Discussion: The findings indicate that audit opinions and audit findings have a positive effect on alleged corruption cases. In contrast, follow-up actions on audit recommendations have a significant adverse effect on alleged corruption cases. These results suggest that audit opinions alone cannot serve as the primary indicator of the effectiveness of local government financial governance. Therefore, the findings of this study provide a basis for policymakers to enhance local government performance evaluation systems that not only emphasise favourable audit opinions but also focus on the effectiveness of audit follow-up and on strengthening internal control systems. Implications: This study provides guidance on the effective implementation of audit recommendations, which can serve as a critical governance mechanism to mitigate corruption risks, improve the efficiency of public resource allocation, and reduce the economic costs associated with governance failures.